The 3 Ts of highly effective supply chains - Wilding, Richard D. (Sckc Cranfield University, 2003)
In recent years the recognition that the supply chain, is a source of competitive advantage has driven organisations to pursue the dual goals of achieving both value advantage and operational excellence. Customer responsiveness is generally the key differentiator in markets today. Globalisation is resulting in many organisations experiencing market pressures that are forcing a fundamental rethink of the way business is conducted. Trade- offs between for example labour costs, transportation costs, inventory costs and response time to customer are becoming increasingly complex. It is no longer seen as possible only to focus on one’s individual organisation to gain competitive advantage. It has been recognised that the success of the individual organisation is dependent on the performance and reliability of its suppliers and also customer